(untitled) (Research, Society and Development, 2022)
Pest mites cause economic damage, so it is essential to know the relationships between pest and predator. For this, a bibliometric review was carried out on the biological control of mites of the Tetranychidae family in agricultural crops. The study was developed using the descriptors “biological control”, “predatory mites”, “Tetranychidae” in the research platforms of the Web of Science, Science Direct, Springer, Scopus and Capes journals, using two methods of analysis: Database through the Microsoft Excel and VOSViewer. In the databases, 2,186 articles were found and 17 were selected. The VOSviewer software grouped 306 articles important to the topic discussed by hundreds of authors, with evidence for food producers. In Microsoft Excel data, the species Tetranychus urticae (pest) and Neoseiulus californicus (predator) were the most cited. Regarding the period of publication, from 2019 to 2021 there was a growth in research with the use of biological control using predatory mites in the control of phytophagous mites of agronomic importance. The analysis shows that this biological control over pest mites has been studied by the academic community, demonstrating the importance of this management.